Corporate responses to community grievance: voluntarism and pathologies of practice - Owen, John R. (Journal of business ethics, 2024)
Grievance landscapes form in rapidly industrialising contexts where social and environmental impacts are inevitable. This paper focuses on the complex operational and organisational settings in which grievances arise and the industrial pathologies that form around resource development projects. The arguments draw on classic and contemporary literature on "grievance", "right" and "entitlement", and the authors' own sustained engagement with global mining companies and local communities. Our contention is that the grievance landscape is far more critical to understanding environmental, human rights, and mining interactions than the managerial systems that companies construct to signal compliance with voluntary international norms. These managerial systems, or operational-level grievance mechanisms, map the procedural contours of how a local grievance would travel once it is made visible to the company. In practice, however, it is fiction, illegibility and invisibility that dominate. Across the pathologies, the common denominator is the corporate propensity to avoid recognising the legitimacy of a local grievance and the source of its cause.